Jahresgaben 1992 : Neuer Aachener Kunstverein. - NAK (Neuer Aachener Kunstverein), Aachen (Aachen : Neuer Aachener Kunstverein, 1992)
Dahn, Walter ; Duchow, Achim ; Erdmann, Andreas ; Ganahl, Rainer ; Lacroix, Peter ; Langanke, Ingrid ; Leisgen, Barbara & Michael ; Loch, Anne ; Monschau, Karl von ; Mulkers, Urbain ; Palmen, Désirée ; Pümpel, Albert ; Vandevelde, Ludwig ; Weiss, Clemens ; Zolper, Heinz
boek